“ Secado de rodajas de piña (ananas comosus) previamente deshidratadas en soluciones osmóticas de sacarosa agua-etanol” - Medina Vivanco, Mari L. (2007)
The advantages of vegetal products and dry fruits are widely known, since when reducing its humidity content, diminishes the microbiological activity remarkably and enzymatic, in addition, the costs of storage and transport diminish. The present work had by objective to obtain pineallpne ?lices (Ananas comosus) dry, smooth cayena variety; using combined processes of osmótica dehydration and drying; sac~arose and ethanol were used like osmodeshidratantes. The next composition of the fresh pineallpne slices with humidity, total proteins, fat, ashes, fiber and carbohydrates of; 87.67 %, 0,14 %, 0,12 %, 0,30 %, 0,39 % and 11,38 % respectively; the ascórbico acid content was of 26,85 mg/1 OOg. Previously to the osmótica dehydration pineallpne slices of 1 ~m of thickness was verified that they are in optima! conditions of freshness, retired the heart, soon they submerged in osmóticas solutions of different concentrations from (water-ethanol-saccharose) and two times of dehydrated (3 and 6 hours). In the drying of pineapple slices the influence of the concentration of the osmóticas solutions was studied (water-ethanol-saccharose) and the temperatures (40, 50 and 60 ºC) through kinetic and the speeds of drying, with sp~ed of 1,0 air of mis. The level of acceptance of the end item was .established by means of sensorial analysis for which a pBCA with semitrained panelistas was used. The kinetic enes of drying as opposed to show the influence of the temperature the osmodeshidratantes, since as the saccharose in the solution is increased, the humidity diminishes, and when increasing the ethanol in the solution the speed of drying increases. By means of these experiments it was determined that the temperature of 40 ºC is not recommendable, being the very slow drying, giving rise to the proliferation of microorganisms, Biochemical and enzyrnatic reactions, harming to the product as far as the final appearance. The temperature of 60 ºC had a behavior in opposition to the one of 40 ºC, because the speed of drying was fast, with the deficiency of which pineallpne slices (Ananas comosus), without osmótico treatrnent and those that they were dehydrated in waterethanol-saccharose solutions (33-33-33) and (34-16-50) they underw~nt abrupt changes in the surface, such as encostramientos and crystallization, settling down that the optima! conditions of drying, were those that were obtained to 50 intermediate temperature of ºC. Of the 16 treatments those that obtained the highest points as far as dried to 50 ºC and dehydrated acceptability were pineapple slices osmóticamente in water-saccharose solutions (50-50), (60-40), without treatment, as well as •pineapple slices dehydrated in water-ethanol-saccharose solutions (34-16-50), being pineapple slices dehydrated with solutions (water-ethanol) those that had minor acceptability degree according to the sensorial analysis.